The Role of Norms in International Relations: A Reflection on the Example of EU External Policy - Skolimowska, Anna (Studia Polityczne, 2025)
The purpose of the article is to show the specificity and importance of the norms factor in contemporary international relations under the conditions of the evolving international order (especially after 2022) with particular emphasis on the specific sub-system of international relations, which is the system of the European Union (EU) under the Common Foreign and Security Policy (CFSP). It is assumed that with the crisis of the liberal international order, the importance and specificity of norms as pillars of the EU strategy in international relations as the main instrument shaping the specificity of actions in the international space within the paradigm of the normative actor is changing. Thus, the question arises whether reference to norms (possibly which ones) can continue to be the basis for building foreign policy assumptions of international actors in the conditions of a return to the rhetoric of force and power politics? The material for analysis will be the strategic documents of the EU’s external policy in the period after 2022–24 in terms of possible actions relating to the response to the changing international reality. The study will be set within the constructivist paradigm.